A scientometric analysis of research on the role of NMDA receptor in the treatment of depression - Chen, Xulin; Wang, Xian; Li, Caijuan; Zhang, Yao; Feng, Shanwu; Xu, Shiqin (Frontiers in Pharmacology, 2024)
There have been numerous studies on NMDA receptors as therapeutic targets for depression. However, so far, there has been no comprehensive scientometric analysis of this field. Thus, we conducted a scientometric analysis with the aim of better elucidating the research hotspots and future trends in this fieldThere have been numerous studies on N-methyl-D-aspartate receptors (NMDARs) as therapeutic targets for depression. A comprehensive scientometric analysis of this area would help to better elucidate research hotspots and future trends.Methods: Publications on NMDAR in Depression between 2004 and 2023 were retrieved from the Web of Science Core Collection (WoSCC) database. Then, VOSviewer, CiteSpace, Scimago Graphica, and R-bibliometrix-were used for the scientometric analysis and visualization.Results: 5092 qualified documents were identified to scientometric analysis. In the past 20 years, there has been an upward trend in the number of annual publications. The United States led the world in terms of international collaborations, publications, and citations. 15 main clusters were identified from the co-cited references analysis with notable modularity (Q-value = 0.7628) and silhouette scores (S-value= 0.9171). According to the keyword and co-cited references analysis, treatment-resistant depression (TRD), ketamine (an NMDAR antagonist), oxidative stress, synaptic plasticity, neuroplasticity related downstream factors like brain-derived neurotrophic factor (BDNF) were the research hotspots in recent years.As the first scientometric analysis of NMDAR in Depression, this study shed light on the development, trends, and hotspots of research about NMDAR in Depression worldwide. The application and potential mechanisms of ketamine in the treatment of major depressive disorder (MDD) MDD are still a hot research topic at present. However, the side effects of NMDAR antagonist like ketamine have prompted research on new rapid acting antidepressants.